Tathbiq istratijiyyah al Ta'lim al Fa'al bi al Khatithah al Dilaliyah al Ta'limiyyah fi Ta'lim Maharat al Kitabah: Dirasah fi al Barnamij al Khas li ta'lim al Lughah al 'Arabiyyah bi Jami'at maulana Malik Ibrahim al Islamiyyah al Hukumiyyah Malang - Rohmatulloh Salis (Tarling : Journal of Language Education, 2022)
This study aims to determine the application of active learning strategy through the Semantic Map Strategy (SMS) in learning writing skills at the Arabic Language Center (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang and students' opinions on the use of it. This research is a qualitative descriptive study. Sources of data in the form of learning curriculum, learning processes, and students. The research instruments are observation and interviews. The data analysis technique used is descriptive qualitative data analysis, namely data reduction, data presentation and drawing conclusions. The results of the study show that: 1) application of active learning strategy through the Semantic Map Strategy (SMS) in learning writing skills was implemented in several stages, namely: (a) introducing the topic (b) brainstorming, (c) categorization, (d) feedback, and (e) arranging semantic maps. 2) all students feel happy and think that the application of active learning strategies through the SMS is very appropriate and effective in teaching writing. This study aims to determine the application of active learning strategy through the Semantic Map Strategy (SMS) in learning writing skills at the Arabic Language Center (PKPBA) Universitas Islam Negeri Maulana Malik Ibrahim Malang and students' opinions on the use of it. This research is a qualitative descriptive study. Sources of data in the form of learning curriculum, learning processes, and students. The research instruments are observation and interviews. The data analysis technique used is descriptive qualitative data analysis, namely data reduction, data presentation and drawing conclusions. The results of the study show that: 1) application of active learning strategy through the Semantic Map Strategy (SMS) in learning writing skills was implemented in several stages, namely: (a) introducing the topic (b) brainstorming, (c) categorization, (d) feedback, and (e) arranging semantic maps. 2) all students feel happy and think that the application of active learning strategies through the SMS is very appropriate and effective in teaching writing.